Climate change impacts and adaptation in U.S. Rocky Mountain high-elevation ecosystems - Meagan F. Oldfather; Alyson Ennis; Brian W. Miller; Kyra Clark-Wolf; Imtiaz Rangwala; Hailey Robe; Caitlin Littlefield (Arctic, Antarctic, and Alpine Research)
From a resource management perspective, climate change is considered to be one of the main threats to high-elevation ecosystems. However, these valuable ecosystems present unique challenges to climate change adaptation (actions in response to environmental change and its effects in a way that seeks to reduce harm) due to their rugged and remote characteristics. Within this context, we summarized literature on climate change impacts and adaptation actions across U.S. Rocky Mountain high-elevation ecosystems to address the important question: What are the knowledge gaps for climate change responses within this ecosystem that limit the ability of natural resource managers to perform successful climate change adaptation? In addressing this question, we focus specifically on the U.S. Rocky Mountains but also place regional conclusions for climate change adaptation in high-elevation ecosystems into a broader context. Overall, we found that the complex topography and temporally variable climate of mountains promote potential refugia that may buffer alpine obligate species in the near-term but also challenge resource managers to consider biological lags within this ecosystem.